COVID-19 and mental health: A systematic review of international medical student surveys - Paz, Dean C.; Bains, Manav Singh; Zueger, Morgan L.; Bandi, Varasiddimounish R.; Kuo, Victor Y.; Cook, Kyle; Ryznar, Rebecca (Frontiers in Psychology, 2022)
The medical school curriculum has imposed psychological stressors on students worldwide, some of which may induce feelings of increased depression and anxiety. Meanwhile, the COVID-19 pandemic has exacerbated the feelings of stress, depression, and anxiety that a portion of medical students experience in their daily life. The aim of this systematic review is to gather concrete data from medical schools around the globe, and further evaluate how the COVID-19 pandemic has impacted medical students’ mental health. Systematic search of data from PubMed, EMBASE, psycINFO, MEDLINE Complete, Google Scholar, and Global Health for studies conducted between December 2019 and July 2021 was conducted. Data from 47 different surveys of medical students from various medical institutions throughout the world were included in this review. These surveys, administered in the form of questionnaires that utilized rating scales, measured anxiety, depression, and stress levels in medical students amidst the COVID-19 outbreak. The COVID-19 outbreak was found to have negative effects on medical students, most notably causing emotional and behavioral changes and detrimental mental health impacts. Higher levels of stress, depression, and anxiety, were found in medical students since the outbreak. This systematic review highlights the sustained high prevalence of moderate depression, anxiety and stress among medical students during the COVID-19 pandemic. Appropriate support and research on which interventions could mitigate these risks is essential in order to ensure that future physicians are properly cared for, and ultimately have the adequate tools needed to provide high quality and empathetic care to future patients.